The Process of Designing an Interactive Website to Understand the Importance of Neutering and Spaying Cat (CatCare) - Azri, Nurul Azrien; Mustafa, Mastika (Journal of Computing Technologies and Creative Content, 2021)
The testicles are removed from the male cat by Neuter, medically known as Orchiectomy. Spay, on the other hand, is known as an ovariohysterectomy that removes the reproductive organs of a female cat. The veterinarian can perform neutering and spaying, or it can be done by a spay and neuter clinic that performs these basic services. Most people knew what neutering and spaying is based on research, but they don’t understand what the importance of neutering and spaying is. The goal of this project is to develop an interactive website capable of providing more information on neutering and spaying cats. Interactive website and PSA videos were developed throughout the project using Sublime 3 Text with PHP, JavaScript and HTML languages and Adobe Premier for video. PhpMyAdmin can integrate with Sublime Text 3 to integrate the website thus handling database storage. In collecting data, the usability testing method is used in which 30 sets of questionnaires are distributed to the respondents. The purpose and aim of the development of this project is accomplished after the data was collected. From the questionnaire, 69.1 % strongly agreed that the existence of this website was able to help society gain more awareness and get a better understanding of neutering and spaying cats. While 69.7% of respondents strongly agreed that this website has easy-to - understand information, and 51.3% agreed that the PSA video provided on the website is more useful in understanding information relating to spaying and neutering cats.